Analisis Pengaruh Penggunaan Chatbot sebagai Asisten Pembelajaran AI terhadap Motivasi Belajar Siswa - Juanta, Palma; Fa, Finley; Alexa, Hipatyah; Andrian, Danil; Sesillya Nababan, Vita (Jurusan Teknik Sipil, Politeknik Negeri Ketapang, 2024)
This study aims to analyze the effect of using chatbots as AI learning assistants on student learning motivation. Chatbots are increasingly recognized as a potential tool in education to increase student motivation and engagement. This study uses an experimental design using the T test as a data analysis method. The sample consisted of two groups, one group that used chatbots in their learning and a control group that did not use chatbots. The T test results showed that the group that used the chatbot experienced a significant increase in learning motivation compared to the control group. This research shows that chatbots can be effective as a motivational tool in educational contexts, with potential implications for application in the development of more student-oriented learning strategies in the future